Implementation of The CSR Program of PT Pertamina Patra Niaga Fuel Terminal Rewulu In Improving The Capacity of Local Food Utilization of Koro Beans - Ichlasia Ainul Fitri; Prasetyo Adi Nugroho; Zukhruf Arifin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Many local food commodities in Indonesia, especially Yogyakarta, are still not utilized into products that are worth selling. This results in the amount continuing to increase in fresh conditions, resulting in a short shelf life. For this reason, through the implementation of the CSR program Pertamina Patra Niaga Fuel Terminal Rewulu together with the academic team aims to 1) increase the use of local food, especially jack beans which are easy to grow in all areas in Bantul, Yogyakarta, 2) Prepare the abilities of members of the Women's Farmers Group (KWT) to be able to process milk from koro beans. The assistance methods used are in the form of socialization, discussion, training and assistance in processing dairy products, as well as evaluation. This activity was carried out in several meetings to ensure that KWT members were able to carry out the processing appropriately. Based on the results of observations, it was found that KWT members were able to practice the training provided and carry out routine production activities during the last three months during the monitoring and evaluation period. It is hoped that through this mentoring activity, KWT members can take advantage of local food which is available in abundance with a higher selling value.